Estudo da contribuição da via entre o hipotálamo dorsomedial e núcleo do trato solitário (HDM-NTS) nas respostas cardiovasculares e comportamentais do quimiorreflexo em ratos não anestesiados - Renata de Bessa Nascimento (2012)
Studies in anesthetized animals have shown that the excitatory amino acid L-glutamate participates in the neurotransmission of the chemoreflex into the nucleus tractus solitarius (NTS). However, in conscious animals, the chemoreflex neurotransmission into the NTS is dependent not only the glutamatergic receptors but also purinergic receptors. The origin of the ATP released into the NTS is not yet known, but studies suggest that stimulation of the hypothalamic defense area (HDA) releases ATP into the NTS. This ATP released into NTS facilitates the chemoreflex cardiorespiratory responses. Previous studies from our laboratory, performed in conscious animals, showed that the dorsomedial hypothalamus (DMH), an integral part of HAD, is involved in the integration of the chemoreflex, since the glutamatergic blockade of the DMH reduced the pressor response and abolished the behavioral response of this reflex. The aim of the present study was evaluate if the activation of the DMH modulates the NTS neurons activity, facilitating the chemoreflex response. This study evaluated the role of purinergic receptors of the NTS in the neurotransmission of the cardiovascular and behavioral responses induced by microinjections of the NMDA or non-NMDA agonists into the DMH. This study also evaluated, in conscious rats, the effect of glutamatergic blockade of DMH and NTS on cardiovascular chemoreflex responses. Male Wistar rats were used, weighting 270-320g. The animals were submitted to stereotaxic surgery to bilateral implant of guide cannulas in direction to DMH and NTS, and also submitted to cannulation of femoral artery and vein, for measurement of cardiovascular parameters and systemic drug injections, respectively. The experiments were recorded by a webcam and the behavioral response was evaluated by the locomotor activity of the animal. The cardiovascular responses induced by the NMDA agonist (10 pmol/100 nl) or the non-NMDA AMPA agonist (3 pmol/100 nl) microinjections into the DHM were evaluated before and 10, 20 and 30 min after the bilateral blockade of purinergic receptors of the NTS with the antagonist Suramin (4 nmol/100 nl). Microinjection of NMDA into the DMH produced increase in arterial pressure (+15 ± 2 mmHg), tachycardia (+80 ± 9 bpm) and behavioral response (187 ± 46 cm). The blockade of the purinergic receptors was able to significantly reduced the pressor response on 20 and 30 min (+2 ± 2 and 6 ± 3 mmHg, respectively), the tachycardic response in all the period studied (+27 ± 13; 21 ±22 and 28 ± 11 bpm, respectively) and the locomotor activity (8 ± 3; 25 ± 9 and cm) induced by the NMDA agonist microinjected into the DMH. The stimulation of the DMH with the AMPA agonist also produced increase in arterial pressure (+16 ± 1 mmHg), tachycardia (+104 ±12 bpm) and behavioral response (276 ± 55 cm). The blockade of purinergic receptors of the NTS was able to reduce only the pressor response induced by the non-NMDA agonist microinjected into the DHM on 10 min (+6 ± 2 mmHg). The locomotor activity induced by AMPA also was reduced at 10 and 20 min (67 ± 26 and 39 ±15 cm, respectively) after Suramin into the NTS. The chemoreflex was stimulated by potassium cyanide (KCN, 40-80 µg/0,1 ml, i.v.) and the reflex responses evaluated before, 5 min after the bilateral microinjection of kynurenic (2,7 nmol/100 nl) into the DMH and 5, 10 and 20 min after the bilateral microinjection of kynurenic (10 nmol/100nl) into the NTS. The chemoreflex stimulation produced increase of arterial pressure (+38 ± 5 mmHg) and bradycardia (-174 ± 28 bpm). As expected, the glutamatergic blockade of the DMH reduced the pressor response (+23 ± 4 mmHg) and produced no changes on bradycardic response (-178 ± 43 bpm) of the chemoreflex. The sequencial blockade of glutamatergic receptors of the NTS produced no additional reduction in the pressor response (5 min: +17 ± 6; 10 min: +20 ± 6 and 20 min: +25 ± 7 mmHg), but reduced the bradycardia 5 and 10 min (-28 ± 17 and -4 ± 15 bpm, respectively) after kynurenic microinjection into the NTS. These data suggest that the cardiovascular and behavioral responses induced by stimulation of glutamatergic receptors into the DMH, particularly the NMDA receptors, seem to be dependent of purinergic receptors of the NTS. However, the release of ATP into the NTS during chemoreflex stimulation seems not directly dependent on stimulation of glutamatergic receptors of the DMH.